Validity and Reliability of Computational Thinking Scales for Undergraduate Students: Indonesian Adaptation - Rizki Hikmawan; Mumu Komaro; Ayi Suherman; Ayu Permata Sari (Didaktika: Jurnal Kependidikan, 2025)
Computational Thinking (CT) is the foundational discipline of informatics. Meanwhile, the Computational Thinking Scale (CTS) is a widely recognized instrument for measuring CT. However, despite its widespread recognition, only a limited number of studies have examined the reliability and construct validity of CTS among Indonesian students. Furthermore, linguistic equivalence across all CTS items is essential to avoid misinterpretation. Therefore, this study aims to adapt the CTS instrument into Bahasa Indonesia and conduct both reliability and validity testing. A total of 551 undergraduate students participated in this research. The statistical methods employed include Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). The results revealed that 9 out of 29 CTS items failed to meet the required criteria. The final model showed strong fit indices (CFI = 0.95, TLI = 0.96, RMSEA = 0.047, SRMR = 0.049), along with acceptable validity and reliability across all dimensions. These findings affirm that the Indonesian version of CTS is a robust and valid tool for assessing students' CT Skills.